Georgiy Yevgeniyevich Sokolovich (to the 75th birthday) - Editorial Article (Бюллетень сибирской медицины, 2006)
The creative biography of retired medical service colonel, doctor of medical sciences, professor of the Siberian State Medical University G.Ye. Sokolovich is presented.